Manajemen Virtual Event Ekrutalks dalam Membangun Citra Perusahaan Berbasis Smart System (Studi Deskriptif Kualitatif pada Ekrutes.Id) - Aini Okta Alfiana; Tria Patrianti (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
The phenomenon of the increase in virtual events after the Covid-19 pandemic has encouraged companies to use them as a communication strategy to strengthen their image in the digital era. Ekrutes.Id, as a technology-based recruitment platform, has taken advantage of this momentum by organizing the Ekrutalks virtual event, which is designed to introduce its services and build the image of a company based on a smart system. This research aims to describe the management of the Ekrutalks virtual event organized by Ekrutes.Id and analyze its role in building the company's image. The research uses a qualitative approach with a descriptive method. Data was collected through interviews, observations, and documentation. Data analysis was conducted using Saiddel's interactive model, which includes the stages of data reduction, data presentation, and conclusion drawing to obtain a comprehensive understanding of the phenomenon being studied. The results of the study indicate that Ekrutalks management runs in accordance with Goldblatt's five stages, namely research, design, planning, coordination, and evaluation. The research stage serves to identify audience needs, while design and planning emphasize creativity in selecting themes, speakers, and digital platforms. Meanwhile, coordination and evaluation are carried out in a structured manner to ensure the sustainability of the event. Through systematic implementation, Ekrutalks is able to build the image of Ekrutes.Id as a professional, adaptive, and technology-based recruitment platform. Thus, virtual events not only serve as a means of communication, but also become an effective strategy in shaping the company's image in the digital era.